Determination of the physical and mechanical properties of recycled low-density polyethylene and biomass composites for use as microbial support media for biological treatment of wastewater - Ramos, Franz Furby C. (2009)
Plastic composites were prepared using recycled low-density polyethylene (rLDPE) and locally available biomass, rice hull charcoal, and coconut shell charcoal at filler loadings of 10 to 60 wt. % Physical, mechanical and micro-structure of their fracture surfaces were investigated in this study. Also, the composite materials were evaluated as support media for biological wastewater treatment by immersing in a reactor under anaerobic condition for 40 days. Based on the results, composites of of increasing filler loading have exhibited increasing density, water absorption and thickness welling. For tensile strength testing, composites with increasing rice hull charcoal and coconut shell charcoal filler loading have increasing tensile strength, about 53% and 43% respectively at 60 wt % filler content; whereas, composite with increasing rice hull content have a decreasing tensile strength to about 9 % at 60 wt % filler content. Micro-structure analysis of the fractured surface showed pull-out traces because of poor bonding between rice hull and rLDPE while tearing of rice hull charcoal and coconut shell charcoal from rLDPE indicated stress transfer of the plastic to the filler resulting to improved mechanical strength. For flexural strength, increasing filler loading has improved composite's flexural strength reaching 158, 255, and 236 % at 60 wt. % rice hull, rice hull charcoal, coconut shell charcoal filler content respectively. After 40 days immersion in wastewater under anaerobic condition, there was no significant change in the mechanical property of the sample composites. Thus, based on the properties and ease of fabrication the most viable ratios as microbial support media are composites at 30 - 50 wt. % filler, rice hull, rice hull charcoal, and coconut shell charcoal, content